2019
DOI: 10.3390/ijerph16193780
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment of Heavy Metals and Lipid Quality Indexes in Freshwater Fish from Lakes of Warmia and Mazury Region, Poland

Abstract: The objectives of study were to determine heavy metals content (Zn, Cu, Mn, Fe and Hg) and fatty acids in selected organs of roach, Rutilus rutilus (L.); bream, Abramis brama (L.); pike, Esox lucius (L.); Eurasian perch, Perca fluviatilis (L.) collected from reservoirs of Warmia and Mazury region (northeastern Poland). Heavy metals were determined with atomic absorption spectrometry AAS. The fatty acids were analyzed using gas chromatography. In a few cases, differences in the content of heavy metals and fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 44 publications
4
22
3
Order By: Relevance
“…As already reported in the literature, these results confirm that Hg has a great potential for bioaccumulation in food chains of aquatic ecosystems and, consequently, in edible fish tissues [54,55]. In general, the concentrations of the tested elements were lower than the ranges recorded in other European water environments, such as lakes of Plumbuita (Romania) and Šalek (Slovenia) and lakes of Warmia and Mazury (Poland) [9,54,56].…”
Section: Hffsupporting
confidence: 84%
See 1 more Smart Citation
“…As already reported in the literature, these results confirm that Hg has a great potential for bioaccumulation in food chains of aquatic ecosystems and, consequently, in edible fish tissues [54,55]. In general, the concentrations of the tested elements were lower than the ranges recorded in other European water environments, such as lakes of Plumbuita (Romania) and Šalek (Slovenia) and lakes of Warmia and Mazury (Poland) [9,54,56].…”
Section: Hffsupporting
confidence: 84%
“…Nevertheless, Li et al [2] found that some freshwater fishes, as do marine fish, possess a higher content of n-3 PUFA, EPA, and DHA in the edible meat and related this to the food habits and trophic levels of the fishes. Despite the widely acknowledged health benefits of fish consumption, some concerns have been raised in relation to the presence of undesired chemical pollutants in fish meat, such as heavy metals, methyl mercury (MeHg), polychlorinated biphenyls (PCBs), dioxins and dioxin-like contaminants (DLCs), organochlorine pesticides, and other environmental contaminants [7][8][9]. Fish products, indeed, are particularly susceptible to contamination, especially those from lentic ecosystems characterized by slow water exchange and elevated anthropization [10].…”
Section: Introductionmentioning
confidence: 99%
“…Roach and perch are the indicator fish of Europe’s freshwater and brackish water. They live in many types of waters and can eat very diverse food, which makes them reflect the cleanliness of the environment they inhabit (e.g., [ 37 , 38 , 39 ]). The health benefits and risks are likely to vary according to the fish species and fish size, harvesting and cultivation practices, and the frequency and amount consumed and the way in which it is served [ 23 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The exceedance of the recommended values of toxic metals set by different regulatory bodies does not always represent the human health risk, and consequently, in recent years, the health risk assessment has been extensively used to evaluate the impact of the hazards of heavy metals bioaccumulation on human health. Assessment of potential risk of heavy metals on human health is evaluated by estimated daily intake, target hazard quotient, and other indexes based on the fish consumption [ 3 , 55 ]. Based on the hazard factor for Hg, Pb, Cd, Ni (THQ < 1), it was found that the consumption of the studied fish does not constitute a carcinogenic health effects.…”
Section: Discussionmentioning
confidence: 99%
“…Fish is regarded as an excellent source of high-quality protein, particularly the essential amino acids lysine and methionine [ 1 , 2 , 3 ]. Globally, they comprise about 6 percent of dietary protein, yet it should be remembered that for some 3 billion people fish make up as much as 20 percent of the average per-capita intake of animal protein [ 4 ].…”
Section: Introductionmentioning
confidence: 99%